2022
DOI: 10.1002/pmic.202100247
|View full text |Cite
|
Sign up to set email alerts
|

Fingolimod effects on the brain are mediated through biochemical modulation of bioenergetics, autophagy, and neuroinflammatory networks

Abstract: Fingolimod (FTY720) is an oral drug approved by the Food and Drug Administration (FDA) for management of multiple sclerosis (MS) symptoms, which has also shown beneficial effects against Alzheimer's (AD) and Parkinson's (PD) diseases pathologies.Although an extensive effort has been made to identify mechanisms underpinning its therapeutic effects, much remains unknown. Here, we investigated Fingolimod induced proteome changes in the cerebellum (CB) and frontal cortex (FC) regions of the brain which are known t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 81 publications
(117 reference statements)
2
6
0
Order By: Relevance
“…We used RNA-seq to comprehensively evaluate the impact of FUS R521H mutation on ROS sensitivity in untreated and SA-treated MNs. We find increased expression of innate immune system components in untreated mutant cells, suggesting that ALS6 MNs exhibit intrinsic inflammation, in accordance with several lines of evidence suggesting toxic effects of the inflammatory response during disease progression (de Boer et al, 2014; Haidet-Phillips et al, 2011; Heitzer et al, 2016; Mirzaei et al, 2022; Potenza et al, 2016). We also find that ALS6 MNs display a lower expression of genes in the TGF-β signaling pathway following SA-treatment.…”
Section: Discussionsupporting
confidence: 90%
“…We used RNA-seq to comprehensively evaluate the impact of FUS R521H mutation on ROS sensitivity in untreated and SA-treated MNs. We find increased expression of innate immune system components in untreated mutant cells, suggesting that ALS6 MNs exhibit intrinsic inflammation, in accordance with several lines of evidence suggesting toxic effects of the inflammatory response during disease progression (de Boer et al, 2014; Haidet-Phillips et al, 2011; Heitzer et al, 2016; Mirzaei et al, 2022; Potenza et al, 2016). We also find that ALS6 MNs display a lower expression of genes in the TGF-β signaling pathway following SA-treatment.…”
Section: Discussionsupporting
confidence: 90%
“…It should be noted that no direct link between ALCs and therapeutic response to fingolimod has been observed, although this drug induces selective changes in blood lymphocytes subsets that were not assessed in this present study ( Boffa et al, 2020 ). Since fingolimod is a lipophilic molecule, it crosses the BBB and may exert protective effects within the CNS by inducing metabolic reprogramming and neuroinflammatory modulation ( Mirzaei et al, 2022 ). Taken together, our data suggest that activation of the PPARγ/CD36 pathway could contribute to the reparative and neuroprotective effects of fingolimod therapy in MS patients.…”
Section: Discussionmentioning
confidence: 99%
“…By inducing internalization and degradation of S1PR1, phospho-FTY720 impairs this egress, resulting in a significant reduction of circulating T and B cells and infiltration in the CNS ( Roy et al, 2021 ). Modulation of S1P receptors present in endothelial cells, neurons, glial cells and the innate immune system may also contribute to the efficacy S1PR-directed therapies in MS ( Thomas et al, 2017 ; Roy et al, 2021 ; Mirzaei et al, 2022 ). Within circulation, S1P is mainly present in high-density lipoprotein (HDL-C), and mediates the regulatory properties of this lipoprotein in immune responses ( Blaho et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that fingolimod counteracts AD-associated neuro-inflammation by regulating the activation of microglia and astrocytes as well as their pro-inflammatory mediators (Aytan et al 2016;Kartalou et al 2020;Mirzaei et al 2022;Rothhammer et al 2017;Zhong et al 2019). Specifically, it is suggested that fingolimod treatment reduces microgliosis and astrogliosis.…”
Section: Fingolimod Receptors and Downstream Signaling Pathwaysmentioning
confidence: 99%